Similar Transition Processes in Synovial Fibroblasts from Rheumatoid Arthritis and Osteoarthritis: A Single-Cell Study - Shaozhe Cai; Bingxia Ming; Cong Ye; Shengyan Lin; Peng Hu; Jungen Tang; Fang Zheng; Lingli Dong (Journal of Immunology Research)
Rheumatoid arthritis (RA) and osteoarthritis (OA) are common rheumatic disorders that primarily involve joints. The inflammation of the synovium can be observed in both of the two diseases. Synovial fibroblasts (SFs) play an important role in the inflammatory process of the synovium. The functional states of synovial fibroblasts are heterogeneous, and the detailed transition process of their functional states is still unclear. By using transcriptomic data of SFs at a single-cell level, we found a similar transition process for SFs in RA and OA. We also identified the potential regulatory effects of the WNT signaling pathway, the TGF-β signaling pathway, the FcεRI signaling pathway, and the ERBB signaling pathway on modifying the SFs’ functional state. These findings indicate potentially overlapped pathogenic mechanisms in these two diseases, which may help uncover new therapeutic targets to ameliorate disease progression.